# consider two polynomials f(x)= x^{3} -2 x^{2} +1/2 and g(x)= x^{3} -3x+1 if f(x) is divided by x+1 to obtain remainder r_{1} and g(x) is divided by (x+2) to obtain remainder r_{2} .find r_{1} ^2+ r_{2} ^2- r_{1} r_{2}

sumithrar4591:
answer plz anybody

## Answers

Answered by

3

Hello

P(x) = x³-2x²+1/2

Divided by x+1

So ,.

By remainder theorem

P(-1) = r1

So

(-1)³-2(-1)²+1/2

= - 1-2+1/2

= 1/2-3 = (-5)/2

g(x) = x³-3x+1

Divided by x+2

By remainder theorem

P(-2) = r2

So

(-2)³-3(-2)+1

= - 8+6+1

= - 2+1

= (-1)

Now ,

R1 =-5/2

R2 = (-1)

So,

R1² + R2²-R1R2

Hope this will be helping you ✌️

P(x) = x³-2x²+1/2

Divided by x+1

So ,.

By remainder theorem

P(-1) = r1

So

(-1)³-2(-1)²+1/2

= - 1-2+1/2

= 1/2-3 = (-5)/2

g(x) = x³-3x+1

Divided by x+2

By remainder theorem

P(-2) = r2

So

(-2)³-3(-2)+1

= - 8+6+1

= - 2+1

= (-1)

Now ,

R1 =-5/2

R2 = (-1)

So,

R1² + R2²-R1R2

Hope this will be helping you ✌️

Similar questions

Environmental Sciences,
13 days ago

English,
1 month ago